A New Crustin Gene Homolog SpCrus8 Identified in Scylla paramamosain Exerting In Vivo Protection Through Opsonization and Immunomodulation - Jiang, Manyu; Chen, Roushi; Chen, Fangyi; Zhu, Xuewu; Wang, Ke-Jian (Frontiers in Immunology, 2022)
Crustins are the most abundant class of antimicrobial peptides in crustaceans and are essential for protecting animals from infection. Among them, type II crustins usually exhibit potent antimicrobial activity. Interestingly, in this study, a newly identified type II crustin gene homolog (named SpCrus8) from mud crab Scylla paramamosain, the recombinant proteins of which (rSpCrus8 and rTrx-SpCrus8) showed no obvious antibacterial effects, but could significantly reduce the bacterial load in crab hemolymph and improve the survival rate of crabs infected with Vibrio alginolyticus. The immune-related function of SpCrus8 and the underlying mechanism deserve further investigation. It was found that the SpCrus8 gene was widely distributed in various tissues of adult crabs. In the hepatopancreas of crabs infected with V. alginolyticus or Staphylococcus aureus, transcripts of the SpCrus8 gene were remarkably induced, indicating that the SpCrus8 gene was involved in the immune response to bacterial infection in vivo. In addition, rSpCrus8 and rTrx-SpCrus8 had strong binding activity not only to microbial surface components (lipopolysaccharide, lipoteichoic acid, peptidoglycan, and glucan), but also to the tested bacteria (S. aureus, Pseudomonas aeruginosa and V. alginolyticus). Notably, rSpCrus8 and rTrx-SpCrus8 could significantly promote hemocyte phagocytosis. After rSpCrus8 and rTrx-SpCrus8 treatment, a large number of fluorescent microspheres were observed to aggregate into clusters and be phagocytosed by multiple hemocytes, while hemocytes in the control group phagocytosed only individual microspheres, indicating that SpCrus8 played an important role in opsonization. When the SpCrus8 gene was knocked down, the expression levels of the key phagocytosis-related genes SpRab5 and SpRab7 were significantly downregulated, as well as the IMD signaling pathway genes SpIKKβ and SpRelish, and another crustin gene SpCrus5. Correspondingly, all the SpIKKβ, SpRelish and SpCrus5 genes were significantly upregulated after rSpCrus8 treatment, suggesting that SpCrus8 might be involved in the immunomodulation of S. paramamosain. Taken together, this study revealed the immune-related functions of the SpCrus8 gene in opsonization and regulation, which will help us further understand the role of the crustin gene family in the immune system of mud crabs and provide new insights into the function of type II crutins.